Restless legs syndrome in end-stage renal disease patients undergoing hemodialysis - Castillo-Torres, Sergio Andrés; Ibarra-Sifuentes, Héctor Raúl; Sánchez-Terán, Helda; Sánchez-Martínez, Concepción; Chávez-Luévanos, Beatriz; Estrada-Bellmann, Ingrid (Arquivos de Neuro-Psiquiatria, 2018)
Restless legs syndrome (RLS) is a frequent complication of hemodialysis that has been associated with poor quality of life and increased risk for complications. Nevertheless, few studies regarding this entity exist in resource-limited settings.Objectives: To determine the prevalence of RLS among Mexican patients on hemodialysis; and compare these patients with a control group of the same population.Methods: We recruited 105 hemodialysis patients. Restless legs syndrome was diagnosed according to the updated criteria set out by the International RLS Study Group. We selected patients who did not meet the criteria, as controls.Results: We found an RLS prevalence of 18%. The RLS patients had a significantly higher prevalence of iron deficiency anemia and uremic pruritus. None of the patients reported RLS symptoms prior to hemodialysis initiation.Conclusions: Restless legs syndrome is common among Mexican patients on hemodialysis. Larger studies are required to address the impact of RLS in hemodialysis patients.
Keywords: Restless legs syndrome; renal dialysis; renal insufficiency